An Examination of the Relationship between Socio-epidemiologic Factors and Positive Workplace Drug Tests in the United States - James Wiiliam Price (Journal of Addiction Medicine and Therapeutic Science - Peertechz Publications, 2016)
Background: An examination of the relationship between social factors and positive workplace drug tests has heuristic value for understanding population vulnerability to subsequent employment disruption. Methods: This is a retrospective analysis using multiple linear regression comparing annual U.S. rates of marriage, divorce, birth, death, mortgage delinquency, disposable income, property crime, violent crime to annual U.S. workplace drug positivity rates (marijuana, opiates, amphetamines, phencyclidine,cocaine) from 1990 to 2012. Results: Significant regression coefficients were demonstrated between several of the dependent and independent variables after adhering to strict inclusion criteria and ruling out multicollinearity and first order linear auto-correlation. United States mortgage delinquency rates correlate with high urine marijuana (β = -0.309, p ≤ 0.05) and cocaine positivity rates (β = -0.732, p ≤ 0.05) for the employed segment of the population. Higher U.S. property crime rates correlate with higher workplace urine amphetamine positivity rates (β = 0.429, p ≤ 0.01). Relatively high national violent crime rates correlate with high urine cocaine positivity rates (β = 0.419, p ≤ 0.05) and low urine amphetamine positivity rates β = -0.929, p ≤ 0.05). High marriage rates correlate with high workplace urine marijuana positivity rates (β = 0.760, p ≤ 0.01) and high U.S birth rates correlate with high workplace urine cocaine positivity rates (β = 0.209, p ≤ 0.05). Conclusions: This study has demonstrated positive and negative associations between the U.S. mortgage delinquency rate, property crime rate, violent crime rate, marriage rate and birth rate with U.S urine drug test positivity rates..